2003
DOI: 10.1080/0899022031000105190
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the functional significance of the neonatal rat vibrissae prior to the onset of whisking

Abstract: The present series of experiments assessed how information from the whiskers controls and modulates infant rat behavior during early learning and attachment. Passive vibrissal stimulation can elicit behavioral activity in pups throughout the first two postnatal weeks, although orienting to the source of stimulation is evident only after ontogenetic emergence of whisking. In addition, while pups were capable of demonstrating learning in a classical conditioning paradigm pairing vibrissa stimulation with electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 53 publications
0
46
0
Order By: Relevance
“…The ubiquity and generality of this trajectory suggest a strong, internally mediated mechanism for patterning spontaneous activity during the development of primary sensory neocortical areas, regardless of the sensory experience of the cortical area during this developmental period. So while sensory input clearly refines cortical circuitry (Trachtenberg et al 2002), the primary drivers of the changes we observed are most likely internal. Because our recordings were performed in the absence of neuromodulators we can reject the hypothesis that the mechanism is primarily neuromodulatory, suggesting a role for changes of synaptic connectivity and neuronal integration in the progression of circuit dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ubiquity and generality of this trajectory suggest a strong, internally mediated mechanism for patterning spontaneous activity during the development of primary sensory neocortical areas, regardless of the sensory experience of the cortical area during this developmental period. So while sensory input clearly refines cortical circuitry (Trachtenberg et al 2002), the primary drivers of the changes we observed are most likely internal. Because our recordings were performed in the absence of neuromodulators we can reject the hypothesis that the mechanism is primarily neuromodulatory, suggesting a role for changes of synaptic connectivity and neuronal integration in the progression of circuit dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…These two areas were selected because they have markedly different developmental timelines: auditory cortex does not receive peripheral input until the cochlea becomes spontaneously active after PND 7 (Sadanaga and Morimitsu 1995), and auditory brain stem responses to external stimuli do not begin until PND 12 (Song et al 2006), while even neonatal pups are capable of using whisker stimulation for a simple classical avoidance conditioning task (Sullivan et al 2003), although active sensation does not occur until the second postnatal week (Mosconi et al 2010). Similarities would suggest a common developmental trajectory that is independent of sensory experience, while differences could be due to outside sensory input or to intrinsic genetic factors.…”
mentioning
confidence: 99%
“…The precocial development of vibrissal touch suggests that it may therefore constitute an important source of sensory information for newborn animals. Sullivan et al (2003) found that, from as early as P3, stimulating the whiskers causes heightened activity in young pups. They respond to passive whisker contacts with head raising, mouthing, and turning towards or away from the stimulus, behaviors that are particularly associated with nipple search and attachment.…”
Section: The Functional Role Of the Mystacial Vibrissae In The First mentioning
confidence: 98%
“…They respond to passive whisker contacts with head raising, mouthing, and turning towards or away from the stimulus, behaviors that are particularly associated with nipple search and attachment. Vibrissal cues have been found to play an important role in nipple attachment (Kenyon, Keeble, & Cronin, 1982;Sullivan et al, 2003), indeed, whisker clipping will cause pups to ''miss'' a nipple more often, particularly in younger pups (P4-6) (Sullivan et al, 2003). In the first post-natal week pups also tend to spend most of their time in litter aggregates, or ''huddles'', as a means of regulating their body temperature (Schank & Alberts, 1997).…”
Section: The Functional Role Of the Mystacial Vibrissae In The First mentioning
confidence: 98%
“…The behavior of pups was recorded prior to stimulation as a baseline and during training using a motor activity scale designed by Hall (Hall 1979). This scale assigns a score for the number of major body parts or regions that moved for at least 2 s. Specific movements such as crawling, head turning toward and away from the stimulation, and mouthing were counted (Sullivan et al 2003). The motor activity scale measures changes in general motor activity as a response of motorically immature rat pups to stimulus presentation (Hall 1979).…”
Section: Classical Conditioning Paradigms Involving Whiskersmentioning
confidence: 99%